2019
DOI: 10.1002/ecs2.2677
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally warmer and drier conditions in an Arctic plant community reveal microclimatic controls on senescence

Abstract: The timing and duration of the plant growing season and its period of peak activity have shifted globally in response to climate change. These changes alter the period of maximum and potential total carbon uptake, especially in highly seasonal environments such as the Arctic. Earlier plant growth has been observed, and if plant senescence remains the same or is delayed, growing season extension will likely lead to greater carbon uptake and growth. We used phenology data from a multifactor climate change experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 86 publications
1
6
0
Order By: Relevance
“…() predicted earlier bud break in a wide range of canopy species with early spring warming. More broadly, climatic warming can also alter the timing of bud‐break and leaf senescence in a variety of plant species, including canopy trees, shrubs, and summer‐green herbaceous plants (Norby et al., ; Jacques et al., ; McDonough Mackenzie et al., ; Rice et al., ; Livensperger et al., ; Zohner and Renner, ). Notably, other studies have demonstrated that plants in arctic, subalpine, and alpine settings can adjust their leaf phenology in response to temperature regime adjustments (Inouye, ; Hoffmann et al., ; Wipf, ; Krab et al., ; Rice et al., ; Richardson et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…() predicted earlier bud break in a wide range of canopy species with early spring warming. More broadly, climatic warming can also alter the timing of bud‐break and leaf senescence in a variety of plant species, including canopy trees, shrubs, and summer‐green herbaceous plants (Norby et al., ; Jacques et al., ; McDonough Mackenzie et al., ; Rice et al., ; Livensperger et al., ; Zohner and Renner, ). Notably, other studies have demonstrated that plants in arctic, subalpine, and alpine settings can adjust their leaf phenology in response to temperature regime adjustments (Inouye, ; Hoffmann et al., ; Wipf, ; Krab et al., ; Rice et al., ; Richardson et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used late winter body mass data of known‐aged female Svalbard reindeer from 1995 to 2019, to test the two hypotheses posited above to explain the positive relationship between higher autumn temperatures and increased late winter body mass. Specifically, we predicted that variation in late winter body mass was explained by an index of plant senescence (derived from the Enhanced Vegetation Index—EVI: Huete et al, 2002), if the relationship between autumn temperature and body mass was driven by prolonged access to high‐quality forage (Livensperger et al, 2019). Alternatively, or in addition, late winter body mass could be explained by onset of snow, if the relationship was driven by availability of forage later into the autumn, rather than strictly by forage quality (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…We revealed a dominant role of mean growing‐season photoperiod in determining the cessation of wood formation across northern conifer species (Figures 3 and 4). The processes underlying the cessation of wood formation have not been fully elucidated, particularly across large geographical scales; probably because the cessation of wood formation is affected in an interactive manner by multiple bioclimatic factors, the species‐specific climate sensitivity, in addition to tree growth‐associated carbon feedbacks (Antonucci et al, 2019; Chen et al, 2019; Dox et al, 2021; Guo et al, 2020; Larysch et al, 2021; Lian et al, 2020, 2021; Livensperger et al, 2019; Way & Montgomery, 2015; Zhang, Belien, et al, 2020; Ziaco et al, 2018). Recent studies have revealed that the temperature response of the cessation of wood formation is counteracted by other factors (Gričar et al, 2022; Gueney et al, 2015; Malik et al, 2020).…”
Section: Discussionmentioning
confidence: 99%